2015
DOI: 10.1101/021147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation-Profile-Based Methods for Understanding Selection Forces in Cancer Somatic Mutations: A Comparative Analysis

Abstract: Human genes exhibit different effects on fitness in cancer and normal cells. Here, we present an evolutionary approach to measure the selection pressure on human genes, using the well-known ratio of the nonsynonymous to synonymous substitution rate in both cancer genomes (C N /C S ) and normal populations (p N /p S ). A new mutationprofile-based method that adopts sample-specific mutation rate profiles instead of conventional substitution models was developed. We found that cancer-specific selection pressure i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 58 publications
(63 reference statements)
1
5
1
Order By: Relevance
“…We observed a greater similarity when we compared our list of negatively selected genes with that of Zhou et al [51]: 32 of the 112 genes identified by Zhou et al,[51] are also present among the 505 negatively selected genes identified in the present work (Supplementary file 3).…”
Section: Negatively Selected Genessupporting
confidence: 59%
See 4 more Smart Citations
“…We observed a greater similarity when we compared our list of negatively selected genes with that of Zhou et al [51]: 32 of the 112 genes identified by Zhou et al,[51] are also present among the 505 negatively selected genes identified in the present work (Supplementary file 3).…”
Section: Negatively Selected Genessupporting
confidence: 59%
“…In summary, the pro-oncogenic, negatively selected genes annotated and validated in the present work are missing from the earlier lists of negatively selected genes [51,66,67,73]. A possible explanation for the lack of similarity of top-ranking negatively selected genes identified in the present study with those identified by others is that we have limited our work to transcripts that have at least 100 somatic mutations.…”
Section: Negatively Selected Genesmentioning
confidence: 57%
See 3 more Smart Citations